Sulam Skills Business Development Emerges in Increasing Family Income (Case Study in Solok Selatan District) - Larasati, Resti; Ismaniar, Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
The background of this research is the embossed embroidery business run by a member of the community, who conducts skills training for housewives. The aim is to improve skills, knowledge, increase family income and prosper the people of Solok Selatan Regency. The aim of the researcher is to describe the process of developing a embroidery skill business starting from communication, training methods and strategies and marketing of embroidery skills products. This research is a research using a qualitative approach, the research method is a case study. The source of the data in this study were housewives in Nagari Pakan Rabaa. South Solok Regency, which manages the emerging embroidery business as research subjects, and members of the emerging embroidery skills as research informants. Data collection techniques in this study are observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and drawing conclusions. Data validity technique is by using source triangulation, technical triangulation and time triangulation. The results of the study show that the process of developing a business with embroidery skills arises starting from a communication strategy, how close and friendly communication is between managers and members. The process of skills training starts from planning, implementation, mentoring, evaluation and follow-up. The marketing strategy for embroidery skills arises starting from paying attention to the quality standards of the results of skills, promotions carried out through the government, members and utilizing social media and the process of establishing partnerships with several companies.Keywords: business development, training and embroidery skills.